1985
DOI: 10.1210/endo-117-3-1222
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Receptors for Insulin and the Insulin-Like Growth Factors on Micro- and Macrovascular Tissues*

Abstract: Insulin and insulin-like growth factors (IGFs) have been implicated in the pathogenesis of diabetic retinopathy and peripheral vascular complications. Previously, we have shown that retinal capillary endothelial cells responded to insulin and IGFs for metabolic and growth effects, whereas aortic endothelial cells were not responsive. In contrast, vascular supporting cells from both retinal capillaries (i.e. pericytes) and aorta (i.e. smooth muscle cells) responded equally to insulin, IGF-I, and IGF-II. The str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
2
2

Year Published

1987
1987
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(44 citation statements)
references
References 32 publications
3
37
2
2
Order By: Relevance
“…This band corresponds to the a subunit ofthe insulin receptor observed in other endothelial or nonendothelial tissues, although the apparent molecular weight of the receptor in endothelial cells is slightly higher than that in nonendothelial tissues. In addition, the major intense band or bands at > 200 kD were found that had been reported by us previously as cross-linked a subunit of the insulin receptor (30). However, affinity labeling studies using divalent agents are not quantitative, because of uncertainty of the cross-linking efficiency in each experiment.…”
Section: Resultsmentioning
confidence: 70%
“…This band corresponds to the a subunit ofthe insulin receptor observed in other endothelial or nonendothelial tissues, although the apparent molecular weight of the receptor in endothelial cells is slightly higher than that in nonendothelial tissues. In addition, the major intense band or bands at > 200 kD were found that had been reported by us previously as cross-linked a subunit of the insulin receptor (30). However, affinity labeling studies using divalent agents are not quantitative, because of uncertainty of the cross-linking efficiency in each experiment.…”
Section: Resultsmentioning
confidence: 70%
“…The binding receptors to epidermal growth factor, including IGFR2, were shown to play a role in the development of microvascular complications in T2D (Jialal et al, 1985). This gene encodes a receptor for both IGF2 and mannose 6-phosphate, which function mainly in immune-or cancer-related disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Insulin receptors (IRs) have been demonstrated on endothelial cells of both large and small blood vessels [119]. The findings that vascular endothelial cell-specific IR knockout mice (VENIRKO) on a low-salt diet showed significant insulin resistance suggest that insulin signaling in endothelial cells participates in the mechanism that correct whole-body insulin sensitivity and vascular function [120].…”
Section: Vascular Endothelial Cellsmentioning
confidence: 99%